'Heimat' in der Literatur der Mennoniten - Stürzebecher, Monika M. (My University, 1987)
This thesis deals with the literature of the Russian Mennonites, who left the Soviet Union for Canada following the upheavals of the Revolution and Civil War. The loss of their homeland - the "Russian Mennonite Experience" - and the building of a new homeland became the central issue of their literature.
The use of Heimat as an approach allows the description of both the concrete loss of the land and its mental implications, thus combining the Mennonite vision with the historical aspect. In defining the Mennonite identity literature plays an instrumental role.
A development can be traced through two generations of writers. In Verloren in der Steppe Arnold Dyck understands Heimat in a rather concrete sense as the Ukrainian steppe and the existence of his people as a "people apart" according to the traditional rules of social interaction. Signs of alienation can be seen in the relationship to the surrounding Russians as well as in the development of the boy Hans as an artist.
Rudy Wiebe's Peace Shall Destroy Many holds a transitional position. In Deacon Block the traditional concept of Heimat fails in the needs of the historical situation as well as of the individual human being. Thom Wiens, however, indicates a positive orientation toward Christ's living and teaching.
In The Blue Mountains of China loss of Heimat is shown in its deepest aspect, the breakdown of the inner spiritual being. At the same time the utopian impulse is the most developed in this novel. Characters like Samuel Reimer or David Epp may fail in what they attempt, their intentions, however, are carried on by others. Caught up in limited perspectives they demonstrate the limitations of human perception. Hence the novel ends "On the way", indicating that true Heimat cannot be reached in this life but is an ideal that transforms the present.
Keywords: German Language and Literature; German Language and Literature